2017
DOI: 10.4236/jcdsa.2017.73020
|View full text |Cite
|
Sign up to set email alerts
|

Skin Damage and Aesthetic Disadvantage Observed in Women in the Hand Craft Shelling Chain of Cashew Nuts in a Factory to Bobo-Dioulasso, Burkina Faso

Abstract: 212 J. Cosmetics, Dermatological Sciences and Applications highly irritating brown oily liquid. Dermatitis occurs during contact with this oily juice. The international literature reports this corrosive effect throughout the history of the chain. Human factors, technical factors and work environment aggravate the situation and compromize workwomen health. Conclusion: Cashew huskers had dermatitis with an impact on daily life. Working conditions and security of employment, hygiene attitudes and anacardic acid w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In a study conducted by Anjana et al found that 17.6% of female cashew workers were suffering from genitourinary infections. 24 Jayakumar reported that as the work increases, the occurrence of urinary infection increases especially in shelling and peeling group women. 16 Current study showed that Respiratory disorders like chronic obstructive pulmonary disease or asthma is frequently seen in shelling group due to increased smoke released while working.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Anjana et al found that 17.6% of female cashew workers were suffering from genitourinary infections. 24 Jayakumar reported that as the work increases, the occurrence of urinary infection increases especially in shelling and peeling group women. 16 Current study showed that Respiratory disorders like chronic obstructive pulmonary disease or asthma is frequently seen in shelling group due to increased smoke released while working.…”
Section: Discussionmentioning
confidence: 99%
“…The fat contents in our samples in this study (47.68% and 42.62%) were close to those reported by Lautié et al [17] which was 46.1%. Fat is a major macronutriment in cashew kernel [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. These fats, 79% of which are in the form of mono-unsaturated fatty acids, as reported by Rico et al [5], they are involved in the prevention of cardiovascular diseases by eliminating LDL cholesterol (bad cholesterol) [5].…”
Section: Discussionmentioning
confidence: 99%
“…Cashew kernels could be employed in food composition as solution to the current food crisis. Moreover, the kernel of the cashew nut is used in cooking under several forms and in cosmetics [16].…”
Section: Introductionmentioning
confidence: 99%
“…They are, however, very prominent as ingredients in PBCA. Moreover, the mostly manual post-harvest processing of cashew nuts has a disastrous impact on the health of the workers, who are mostly uneducated women whose voices are rarely heard in mainstream attention [29]. Therefore, to achieve a new cheese alternatives which can truly be considered sustainable, the ingredients for PBDA should be carefully selected in the perspectives of low environmental and social impact as well as local production.…”
Section: Introductionmentioning
confidence: 99%